Contemporary Christian travel : pilgrimage, practice and place - ʻAmos Ron; Dallen J. Timothy (Bristol, United Kingdom : Channel View Publications, 2019)
This book is the first to examine the complexity of global Christian travel and how it manifests in terms of both supply and demand. It considers the places and spaces of production and consumption of this increasingly important tourism phenomenon and includes examples from Europe, the Middle East, Asia, Africa, Latin America and North America
Keywords: BUSINESS & ECONOMICS / Industries / Hospitality; Travel Religious aspects Christianity; RELIGION Holidays Christian; Travel & Tourism